CDNA-CCS: Splitting and compression based chaotic-DNA cryptography framework for cloud computing security - Jero, J.R. Ancy; Misbha, D.S. (Knowledge-based systems, 2025)
Cloud-computing security is a topic of ongoing research, however, when it comes to data sharing, the main disadvantage is that different users may have data overlap because multiple users save their data on cloud servers. So, the proposed work is to create an improved Cloud Computing Security (CSS) model to protect the data from different threats and reduce overlapping possibilities. SHA-512/256 is designed to produce a fixed-length hash from the user identity data. Further, the data is compressed using Deflate compression, thus reducing the storage space consumption by reducing the byte size. Then, the data are moved to encryption processing; here, hybrid Chaotic-DNA (CDNA) encryption is utilized for encryption purposes. In the Chaotic-DNA process, the data are encrypted based on chaotic workflow, but for an effective security process, a DNA-based key generation is provided. According to the data's level of sensitivity, the key for the hybrid encryption scheme was generated by a trusted centre in the cloud. If the user wants to access the stored data from the cloud system, they must cross four authentication barriers: password, user ID, OTP and fingerprint. The proposed model provides a 98% security level and a 2-second authentication process. For evaluating the proposed-model under various data like image data, text data and integer data. In that image, data takes 90 sec for encryption and 0.18 sec for decryption time, text data takes 149 sec for encryption and 0.69 sec for decryption time, and integer data takes 101 sec for encryption and 1.4 sec for decryption time. This experimental study demonstrates that the recommended security method drastically lowers overlap and effectively reduces space utilization.